2010
DOI: 10.3109/09537104.2010.510894
|View full text |Cite
|
Sign up to set email alerts
|

Long term changes in platelet counts afterH. pylorieradication in non-ITP patients

Abstract: Helicobacter pylori eradication is becoming a first-line therapy against idiopathic thrombocytopenic purpura (ITP) and its long term efficacy has already been reported. In contrast, eradication therapy reduced peripheral platelets in non-ITP patients 8 weeks later. To confirm the long term efficacy of Helicobacter eradication on platelet counts in non-ITP patients, we evaluated changes in peripheral platelet counts in endoscopically diagnosed patients with Helicobacter infection. Endoscopically diagnosed patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…In addition, we previously reported a reduction in peripheral platelet counts of around 2.0 × 10 9 /l after eradication therapy unaware of any sex difference [3]. The previous reports and the current data indicate that females showed higher platelet counts by 2–4 × 10 9 /l than males [4,6,8,10,11,15,16,17,18].…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In addition, we previously reported a reduction in peripheral platelet counts of around 2.0 × 10 9 /l after eradication therapy unaware of any sex difference [3]. The previous reports and the current data indicate that females showed higher platelet counts by 2–4 × 10 9 /l than males [4,6,8,10,11,15,16,17,18].…”
Section: Discussionmentioning
confidence: 50%
“…Eradication of Helicobacter pylori is now accepted as a first-line therapy in patients with idiopathic thrombocytopenic purpura [1], whereas such treatment can decrease peripheral platelet counts in non-idiopathic thrombocytopenic purpura patients [2,3]. Many factors have been reported to influence peripheral platelet counts, such as smoking, sex difference, ethnicity and others [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…focused on a peculiar interaction between H. pylori infection and peripheral platelet count in patients without ITP. In particular, the authors reported a significant decrease in peripheral platelet counts in patients with H. pylori infection, after its successful eradication [15]; the clinical significance of such a phenomenon is still unclear. A study conducted by Gursel et al.…”
Section: Hematologic Diseasesmentioning
confidence: 99%
“…A significant drop in peripheral blood platelet counts was observed in non-ITP patients [16]. Our patient group had not any primary of secondary disease which might affect platelet counts, and they had not received H. pylori eradication therapy.…”
Section: Discussionmentioning
confidence: 94%